2013
DOI: 10.1890/es12-00314.1
|View full text |Cite
|
Sign up to set email alerts
|

Plant community structure mediates potential methane production and potential iron reduction in wetland mesocosms

Abstract: Abstract. Wetlands are the largest natural source of methane to the atmosphere, but factors controlling methane emissions from wetlands are a major source of uncertainty in greenhouse gas budgets and projections of future climate change. We conducted a controlled outdoor mesocosm experiment to assess the effects of plant community structure (functional group richness and composition) on potential methane production and potential iron reduction in freshwater emergent marshes. Four plant functional groups (facul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…However, other studies found that the presence of plants in flooded wetlands or ponds enhanced CH 4 emissions (van Groenigen et al, 2011;Andrews et al, 2013;Mozdzer and Megonigal, 2013). Our results were consistent with the latter findings, possibly because CH 4 oxidation was suppressed, leading to dominance of CH 4 transport under the anaerobic conditions that occur in flooded environments (Bhullar et al, 2013).…”
Section: Effects Of Vegetation On Greenhouse Gas Emissions In Createdsupporting
confidence: 91%
See 1 more Smart Citation
“…However, other studies found that the presence of plants in flooded wetlands or ponds enhanced CH 4 emissions (van Groenigen et al, 2011;Andrews et al, 2013;Mozdzer and Megonigal, 2013). Our results were consistent with the latter findings, possibly because CH 4 oxidation was suppressed, leading to dominance of CH 4 transport under the anaerobic conditions that occur in flooded environments (Bhullar et al, 2013).…”
Section: Effects Of Vegetation On Greenhouse Gas Emissions In Createdsupporting
confidence: 91%
“…Many studies also showed that plants can influence the quantity of greenhouse gases emitted to the atmosphere by affecting gas production, consumption, and transport (Andrews et al, 2013;Koelbener et al, 2010;Picek et al, 2007). However, salinity factor could adjust the effects of plants on greenhouse gas emissions (Munns and Tester, 2008;Tavakkoli et al, 2011;Feng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Wetland vegetation species could also be an important factor driving the variation in methanogen community composition and methanogenesis (Andrews et al, 2013;Zhang, Liu, et al, 2018;Zhang et al, 2019). We found differences in the abundance distribution and composition of the methanogenic communities according to wetland type.…”
Section: Discussionmentioning
confidence: 72%
“…When we applied 2, 4, and 8 Mg ha −1 of steel slag in our plots, there was a corresponding supply of additional Fe at a rate of 67.2, 134, and 269 kg ha −1 , respectively, mainly in the oxidised form such as Fe 2 O 3 . Given that Fe 3+ is thermodynamically more favourable alternative electron acceptor than CO 2 or acetate (Chidthaisong and Conrad, 2000), the increased availability of Fe 3+ helps to suppress the activity of methanogens, the addition of Fe 3+ increase the soil reduction capacity and becomes the main electron acceptor (Van Bodegom and Stams, 1999), and iron reducing bacteria thus tend to outcompete methanogens (Andrews et al, 2013). Moreover, in addition to reducing methane synthesis, Fe 3+ can increase existing methane oxidation and the slag porous structure increases soil microbial activity of methanotrophs.…”
Section: The Effect Of Steel Slag On Ch 4 Emissionmentioning
confidence: 99%